Метод оценки температурных сдвигов полос в электронных спектрах паров молекул по их спектрам в жидких растворах - Арьев, И.А.; Лебовка, Н.И.; Огенко, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
A new method for estimation of the temperature dependence of bands in electronic spectra of
molecules in the gas phase based on their electronic spectra in neutral solutions is proposed.
The method is used for solutions of fullerene C60 in liquid n-heptane.